2010
DOI: 10.1068/a41405
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the School Journey: Integrating Data on Travel and Environment

Abstract: Introduction and contextIn the developed world most children between the ages of 5 and 16 travel to and from school each weekday and, during term time, such trips comprise a significant amount of the total movement of people and vehicles that occurs in urban areas. For instance, travel for education accounted for some 6% of all journeys made in Britain in 2006; and for those under 17 this category represented 27% of all journeys (Department for Transport, 2006). Such movement has a wide range of social, econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Panter et al, (2008) have also discussed how possible motivational elements on the school journey, such as a friend's house or shops to visit en route or parks to play in, might influence the travel mode. Indeed, empirical evidence from a small study using mobile phones and GPS devices to understand children's perceptions of their school journey (Pooley et al, 2010) supports this view of the importance of the child's own motivation to move in the environment, as it was found that pupils who travelled independently were most likely to engage with their immediate environment.…”
Section: Discussionmentioning
confidence: 70%
“…Panter et al, (2008) have also discussed how possible motivational elements on the school journey, such as a friend's house or shops to visit en route or parks to play in, might influence the travel mode. Indeed, empirical evidence from a small study using mobile phones and GPS devices to understand children's perceptions of their school journey (Pooley et al, 2010) supports this view of the importance of the child's own motivation to move in the environment, as it was found that pupils who travelled independently were most likely to engage with their immediate environment.…”
Section: Discussionmentioning
confidence: 70%
“…Studies following objects include the novel work of Böge (1995) who traced all the components of a yoghurt pot to show the mobilities or food miles intrinsic in everyday consumption. González et al (2008) traced human movements using GIS records from mobile phones while the work of Mackett et al (2008) and Pooley et al (2010) used GIS to trace participants and interview them about their activities and hence their exposure to pollutants or levels of physical activity. Then there is the more ethnographic based work such as that of Bissel (2009, Jones et al (2008), Kusenbach (2003), Hodgson and Grieco (2008), and Hodgson (forthcoming) in which interviews are conducted whilst walking and observations made of the interaction of the interviewer and the participant in the walking environment.…”
Section: Introductionmentioning
confidence: 99%
“…To make sense of, and gain better understandings of, children's everyday life, studies have followed children with a GPS tracker (Alarasi, Martinez, and Amer 2015;Ergler 2011;Loebach and Gilliland 2010;Walker et al 2009), videoed and photographed children's routes to school (Kullman 2012;Pooley et al 2010) or engaged in participatory videoing or Soft (qualitative) GIS for representing young people's lives in a neighbourhood (Blazek and Hraňová 2012;Kytta 2011). Researchers have also used Facebook and Twitter as discussion forums and phones to respond to surveys or interventions (Korson 2014;Lim et al 2008;Luh Sin 2015).…”
Section: Using Digital Technologies In Research With Children and Youmentioning
confidence: 99%